Functions of G protein‐coupled receptor 56 in health and disease. (22nd August 2022) - Su, Tiantian; Guan, Qiuyun; Cheng, Huijuan; Zhu, Zhenduo; Jiang, Chunru; Guo, Paipai; Tai, Yu; Sun, Hanfei; Wang, Manman; Wei, Wei; Wang, Qingtong
Abstract: Human G protein‐coupled receptor 56 (GPR56) is encoded by gene ADGRG1 from chromosome 16q21 and is homologously encoded in mice, at chromosome 8. Both 687 and 693 splice forms are present in humans and mice. GPR56 has a 381 amino acid‐long N‐terminal extracellular segment and a GPCR proteolysis site upstream from the first transmembrane domain. GPR56 is mainly expressed in the heart, brain, thyroid, platelets, and peripheral blood mononuclear cells. Accumulating evidence indicates that GPR56 promotes the formation of myelin sheaths and the development of oligodendrocytes in the cerebral cortex of the central nervous system. Moreover, GPR56 contributes to the development and differentiation of hematopoietic stem cells, induces adipogenesis, and regulates the function of immune cells. The lack of GPR56 leads to nervous system dysfunction, platelet disorders, and infertility. Abnormal expression of GPR56 is related to the malignant transformation and tumor metastasis of several cancers including melanoma, neuroglioma, and gastrointestinal cancer. Metabolic disorders and cardiovascular diseases are also associated with dysregulation of GPR56 expression, and GPR56 is involved in the pharmacological resistance to some antidepressant and cancer drug treatments. In this review, the molecular structure, expression profile, and signal transduction of GPR56 are introduced, and physiological and pathological functions of GRP56 are comprehensively summarized. Attributing to its significant biological functions and its long N‐terminal extracellular region that interacts with multiple ligands, GPR56 is becoming an attractive therapeutic target in treating neurological and hematopoietic diseases.